Throwing technique and efficiency in the 2013 British judo championships - Miller, G. A; Collins, N. A; Stewart, M. J; Challis, D. G (International Journal of Performance Analysis in Sport, 2015)
In order to quantify the use of technical throwing techniques in British Judo, the 2013 Junior and Senior British Championships were subject to analysis. 292 competitors of differing age and gender, competing in 558 contests under the 2010 - 2012 IJF rules, were analysed using SportsCode Pro software and publically available video footage. The overall aim was to develop a technical profile for standing techniques in British Judo, looking primarily at technique type and throw efficiency. The data exemplified that British judoka most effectively use foot techniques (ashi-waza) to obtain scores, with uchi-mata (inner thigh throw) proving to be the most efficient technique in the British repertoire. Males and females, juniors and seniors execute differing techniques; however only junior males provided data that didn't match the overall trend, with te-waza (hand throws) and seoi-nage (shoulder throw) being the highest scoring and most efficient.